A polymorphism in the glucocorticoid receptor gene is associated with refractory hypotension in premature infants - Kei Ogasawara; Maki Sato; Koichi Hashimoto; Takashi Imamura; Hayato Go; Mitsuaki Hosoya (Pediatrics and Neonatology)
Glucocorticoids play an important role in endocrine control. The association of glucocorticoid receptor (GR) gene polymorphisms with altered sensitivity to glucocorticoid therapy has been reported in adults. However, there are few such reports in infants. The present study analyzed the prevalence of four GR polymorphisms in preterm infants born before 30 weeks of gestation and determined the associations between these polymorphisms and clinical outcomes in the infants. Methods: Totally, 41 preterm infants born at two hospitals in Fukushima were retrospectively screened for the presence of four GR gene polymorphisms, using a TaqMan single-nucleotide polymorphism genotyping assay. The effect of GR gene polymorphisms on clinical outcomes during hospitalization was evaluated. The following primary clinical outcomes were assessed: refractory hypotension in the acute phase and/or severe bronchopulmonary dysplasia, maximum dopamine and dobutamine doses administered, and total hydrocortisone dose administered in the first 48 h of life. Multivariate analysis with logistic regression was used to assess the association between clinical factors and refractory hypotension. Results: Of the four GR polymorphisms, only the BclI polymorphism was detected. The genotype distribution was as follows: C/C, 33; C/G, 8; and G/G, 0 infants. Significant differences were observed between the C/C and C/G genotypes with respect to the following variables: refractory hypotension (6% vs. 50%), dopamine dose [3.0 (2.0–4.0) vs. 4.8 (4.0–7.5) μg/kg/min], dobutamine dose [2.4 (0.0–3.6) vs. 4.0 (0–10.0) μg/kg/min], and total hydrocortisone dose administered in the first 48 h of life [2.0 (0–10.0) vs. 6.0 (0–12.0) mg/kg]. Multivariate analysis showed that the BclI genotype (C/C) was significantly less associated with refractory hypotension in the acute phase (odds ratio, 0.008; 95% confidence interval, 0.000–0.371; p = 0.013). Conclusion: The incidence of refractory hypotension in infants with the C/C genotype was initially expected to be higher than that in infants with the C/G genotype. However, the results of this study were rather different from what we originally expected. The suppressive effect of antenatal steroid use on the HPA axis of the preterm infants with the BclI variant may be associated with refractory hypotension in the acute phase.